Currency cycles and the international economy - BIASCO, S. (PSL Quarterly Review, 2013)
The intrinsic factors which cause a key currency to move persistently in one direction are analysed, as well as those phenomena which develop as an endogenous consequence of the process of appreciation or depreciation changing the characteristics and ultimately the direction of the process. The author refers essentially to the relationship of the Mark to the dollar between 1975 and present day, as the axis around which the whole world economy has been revolving. The paper focuses on a stylised succession of causal relationships that can serve as an analytical and conceptual framework for understanding the forces that act on a key currency in periods of widespread fluctuation, without dwelling on the descriptive statistical basis of each assertion. JEL: F20, F30